STRUKTUR, UNSUR, DAN EJAAN BAHASA INDONESIA DALAM TEKS FABEL KARYA SISWA KELAS VII SMP NEGERI 12 PADANG - GUSTI REZA PAHLEVI (Universitas Negeri Padang, 2021)
The purpose of this study were threefold, namely, first to describe the text structure of the fable written by grade VII students of SMP Negeri 12 Padang. Second, to describe the elements of the text of the fable written by the VII grade students of SMP Negeri 12 Padang. Third, to describe the use of EBI in the fable text created by grade VII students of SMP Negeri 12 Padang. The data in this study is an analysis of the structure, elements, and spelling of Indonesian in the text of the fable created by grade VII students of SMP Negeri 12 Padang. Based on the results of the research that has been analyzed, it can be concluded that three things are: First, in writing fable texts, seventh grade students of SMP Negeri 12 Padang have used the four fable text structures, namely orientation, complications, resolution, and code. Second, in terms of elements, grade VII students of SMP Negeri 12 Padang have used the right elements. Third, in terms of spelling, grade VII students of SMP Negeri 12 Padang are generally unable to use EBI correctly. Many mistakes occur when writing capital letters, commas, and periods.